2022
DOI: 10.1039/d2cp00918h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh mechanical flexibility induced superior piezoelectricity of InSeBr-type 2D Janus materials

Abstract: InSeBr-type monolayers, the ternary In(Se,S)(Br,Cl) compounds, are typical two-dimensional (2D) Janus materials and can be exfoliated from their bulk crystals. The structural stability, electronic property, mechanical flexibility, and intrinsic piezoelectricity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…5(c). The results indicate that W 4 PCl 11 monolayer can sustain the critical tensile strains of 13% and 15% in the x and y directions, respectively, which are comparable to those of MoS 2 (6–11% or 22.5%) 51,52 and α-boron (12% and 16%), 53 but still smaller than those of graphene (19.4% and 26.6%), 54 phosphorene (27% and 30%), 55 InSeBr (21% and 33%), 15 and Si 2 Te 3 (38%). 56 Thus, such critical tensile strains should be carefully considered in device applications for W 4 PCl 11 monolayer to avoid mechanical fatigue and damage.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…5(c). The results indicate that W 4 PCl 11 monolayer can sustain the critical tensile strains of 13% and 15% in the x and y directions, respectively, which are comparable to those of MoS 2 (6–11% or 22.5%) 51,52 and α-boron (12% and 16%), 53 but still smaller than those of graphene (19.4% and 26.6%), 54 phosphorene (27% and 30%), 55 InSeBr (21% and 33%), 15 and Si 2 Te 3 (38%). 56 Thus, such critical tensile strains should be carefully considered in device applications for W 4 PCl 11 monolayer to avoid mechanical fatigue and damage.…”
Section: Resultsmentioning
confidence: 85%
“…5(c), we obtain two very small critical stresses of 1.9 and 1.5 N m −1 in the x and y directions, respectively. Such ideal strengths of W 4 PCl 11 monolayer are much lower than those of most reported 2D materials, such as α-boron (12.8 and 16 N m −1 ), 53 MoS 2 (15 N m −1 ), 52 and Si 2 Te 3 (8.63 N m −1 ), 56 phosphorene (4 and 10 N m −1 ), 55 BN (23.56 and 7.82 N m −1 ), 57 InSeBr (4.94 and 4.72 N m −1 ), 15 and g-ZnS (5.2 and 5 N m −1 ), 58 suggesting that W 4 PCl 11 monolayer is an extremely flexible 2D material and may have potential applications in the electronic and photoelectric devices with the flexibility requirements.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinctive properties exhibited by two-dimensional (2D) materials have attracted substantial interest from researchers. Compared with bulk materials, 2D materials exhibit excellent mechanical strength, 10 flexibility, 11,12 and ultra-large specific surface area. 13,14 Among them, single-atomic-layer MoS 2 have been proven theoretically and experimentally to possess strong in-plane piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…Since the Janus MoSSe and WSSe have been synthesized experimentally, 23,24 a large number of 2D Janus materials deriving from group VIB transition metal dichalcogenides and group III-VI metal chalcogenides are proposed and widely studied, such as Janus MXY (M = Mo and W; X a Y= S, Se, and Te), Janus PtX n Y 2Àn (X, Y = S, Se, Te; 0 r n r 2) and Janus M 2 XY (M = Ga and In; X a Y = S, Se and Te), 25,26 which exhibit many novel physical properties, including large Rashba spin splitting, 27,28 high carrier mobility and high storage capacity, 29 efficient photocatalytic water splitting 30 and enhanced in-plane and out-of-plane piezoelectric coefficients. [31][32][33] Inspired by these findings, researchers have begun to focus their attention to 2D Janus group IV-V compounds. Tug ˘bey Kocabaset al showed by using a high-throughput method that materials containing group V elements produce significantly high piezoelectric strain constants.…”
Section: Introductionmentioning
confidence: 99%